Across-frequency combination of interaural time difference in bilateral cochlear implant listeners - Ihlefeld, Antje; Kan, Alan; Litovsky, Ruth Y. (Frontiers in Systems Neuroscience, 2014)
The current study examined how cochlear implant (CI) listeners combine temporally interleaved envelope-ITD information across two sites of stimulation. When two cochlear sites jointly transmit ITD information, one possibility is that CI listeners can extract the most reliable ITD cues available. As a result, ITD sensitivity would be sustained or enhanced compared to single-site stimulation. Alternatively, mutual interference across multiple sites of ITD stimulation could worsen dual-site performance compared to listening to the better of two electrode pairs. Two experiments used direct stimulation to examine how CI users can integrate ITDs across two pairs of electrodes. Experiment 1 tested ITD discrimination for two stimulation sites using 100-Hz sinusoidally modulated 1000-pps-carrier pulse trains. Experiment 2 used the same stimuli ramped with 100 ms windows, as a control condition with minimized onset cues. For all stimuli, performance improved monotonically with increasing modulation depth. Results show that when CI listeners are stimulated with electrode pairs at two cochlear sites, sensitivity to ITDs was similar to that seen when only the electrode pair with better sensitivity was activated. None of the listeners showed a decrement in performance from the worse electrode pair. This could be achieved either by listening to the better electrode pair or by truly integrating the information across cochlear sites.